2010
DOI: 10.1210/jc.2009-2309
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status and Its Relation to Muscle Mass and Muscle Fat in Young Women

Abstract: We found that vitamin D insufficiency is associated with increased fat infiltration in muscle in healthy young women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
77
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(89 citation statements)
references
References 57 publications
8
77
4
Order By: Relevance
“…One of these lines found that low serum levels of vitamin D are associated with higher levels of infiltration of fat in muscle in young women (Gilsanz et al, 2010). The other line of research found that low levels of serum vitamin D were associated with low levels of grip strength in adolescent and young adult females (Foo et al, 2009;von Hurst et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…One of these lines found that low serum levels of vitamin D are associated with higher levels of infiltration of fat in muscle in young women (Gilsanz et al, 2010). The other line of research found that low levels of serum vitamin D were associated with low levels of grip strength in adolescent and young adult females (Foo et al, 2009;von Hurst et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…They involve the rapid regulation of membrane calcium channels, suggesting a role for vitamin D in the calcium‐mediated muscle functions, such as muscle contraction and mitochondrial function, which leads to an adequate insulin signalling and muscle substrate metabolism 42. All these findings may clarify the relationship between low vitamin D status and muscle weakness,37, 43 intramuscular fat deposition,44 and resistance to insulin,45 which is related to cardiovascular risk and increased skeletal muscle breakdown 46. Of note, skeletal muscle may also act as a storage site for vitamin D, as recently described 10…”
Section: Vitamin D Physiologymentioning
confidence: 99%
“…Subjects with mutations of the VDR or severe vitamin D deficiency show generalized muscle atrophy, even before biochemical signs of bone disease appear 36, 47. Changes in muscle morphology include derangement of the intermyofibrillar network, increases in intramuscular lipids, and atrophy of the fast‐twitch white (type 2) fibres,11, 44, 48, 49 which are the first to be recruited when preventing a fall. All these changes seem to be reversible,50 supporting co‐ordinated effects of vitamin D in musculoskeletal physiology 51, 52, 53, 54…”
Section: Vitamin D Physiologymentioning
confidence: 99%
“…The latter is related with vitamin D since in the deficient state, it has been reported that there is increased fat infiltration in the muscle. This physiological mechanism is associated with lower levels of muscle strength and physical performance, independent of muscle mass [172]. To date, a number of organizations recognize that vitamin D is directly related with the falls in the elderly, including the International Osteoporosis Foundation, the Endocrine Society, and the US Preventive Services Task Force [173].…”
Section: Vitamin D In Non-athletesmentioning
confidence: 99%